Techniques to Ensure Accurate Targeting for Delivery of Awake Laser Interstitial Thermotherapy. Issue 4 (10th February 2018) - Laurent, Dimitri; Oliveria, Seth F; Shang, Michael; Bova, Frank; Freedman, Rachel; Rahman, Maryam
Abstract: BACKGROUND: Magnetic resonance imaging (MRI) guided laser interstitial thermal therapy (LITT) is an emerging neurosurgical treatment modality that is typically performed under general anesthesia. We describe a novel workflow developed at the University of Florida to deliver LITT in conscious patients without the use of general anesthesia. OBJECTIVE: To describe a novel workflow for LITT implementation in the awake patient with equivalent treatment results when compared to procedures performed under general anesthesia. METHODS: For trajectories near a post of the Cosman-Roberts-Wells (CRW) frame (Integra LifeSciences, Plainsboro, New Jersey), we used preoperative MRI imaging to 3-dimensional-print a patient-specific mask with a trajectory guide to indicate the planned entry point during headframe placement. Otherwise, routine headframe placement and stereotactic registration were performed. Stereotactic biopsy and placement of the cranial bolt were performed in a standard neurosurgical operating room. The patient was transferred to a diagnostic MRI suite and positioned in the MRI scanner using beanbags and a custom molded thermoplastic mask. LITT was delivered with the patient conscious in the MRI scanner according to the manufacturer's recommendations. We collected patient demographics, treatment time, length of stay, and calculated preoperative tumor volume and postoperative ablation volumes. RESULTS: Ten sequential patients were treated with LITT from January 2016 until March 2017. The average preoperative tumor volume was 6.9 cm 3 . The average tissue volume ablated was 18.3 cm 3 . The mean operative time was 31 min (standard deviation [SD] 10 min) and mean time with laser delivery in MRI was 79 min (SD 27 min). The mean length of stay was 1.4 d (SD 0.9). There were no major complications. CONCLUSION: Using trajectory preplanning, customized face masks, and noninvasive head immobilization, LITT can be delivered to patients safely and accurately without general anesthesia.